hiPSC-Derived Epidermal Keratinocytes from Ichthyosis Patients Show Altered Expression of Cornification Markers - Lima Cunha, Dulce (Int J Mol Sci, 2021)
Inherited ichthyoses represent a large heterogeneous group of skin disorders characterised by impaired epidermal barrier function and disturbed cornification. Current knowledge about disease mechanisms has been uncovered mainly through the use of mouse models or human skin organotypic models. However, most mouse lines suffer from severe epidermal barrier defects causing neonatal death and human keratinocytes have very limited proliferation ability in vitro. Therefore, the development of disease models based on patient derived human induced pluripotent stem cells (hiPSCs) is highly relevant. For this purpose, we have generated hiPSCs from patients with congenital ichthyosis, either non-syndromic autosomal recessive congenital ichthyosis (ARCI) or the ichthyosis syndrome trichothiodystrophy (TTD). hiPSCs were successfully differentiated into basal keratinocyte-like cells (hiPSC-bKs), with high expression of epidermal keratins. In the presence of higher calcium concentrations, terminal differentiation of hiPSC-bKs was induced and markers KRT1 and IVL expressed. TTD1 hiPSC-bKs showed reduced expression of FLG, SPRR2B and lipoxygenase genes. ARCI hiPSC-bKs showed more severe defects, with downregulation of several cornification genes. The application of hiPSC technology to TTD1 and ARCI demonstrates the successful generation of in vitro models mimicking the disease phenotypes, proving a valuable system both for further molecular investigations and drug development for ichthyosis patients.